The effect of continuous positive airway pressure therapy on atrial fibrillation in patients with obstructive sleep apnea - Hu, Jiancheng; Zuo, Siyuan; Qian, Jiahui; Cheng, Fangfang; Wang, Dengji; Deng, Yanyan; Lu, Dasheng (Frontiers in Medicine, 2025)
Obstructive sleep apnea (OSA) stands as an autonomous risk factor for a broad spectrum of cardiovascular diseases, particularly atrial fibrillation (AF), which is closely associated with heightened morbidity and mortality rates. The intricate pathophysiological pathways linking OSA to AF encompass chronic intermittent hypoxia, disruptions in the autonomic nervous system, inflammatory responses, and alterations in ion channel function. Continuous positive airway pressure (CPAP) therapy emerges as the frontline treatment for moderate to severe OSA, effectively alleviating symptomatic manifestations and potentially mitigating cardiovascular risks. However, the influence of CPAP on AF among OSA patients remains a subject of debate. Some investigations underscore its beneficial effects, including the reversal of atrial remodeling, enhanced atrial conduction, decreased AF incidence, and improved outcomes post-AF ablation in CPAP-treated individuals. Conversely, other studies reveal neutral or insignificant impacts. This review delves into the repercussions of CPAP therapy on AF in OSA patients, exploring potential explanations for the discrepancies observed across existing research endeavors. By consolidating current evidence and pinpointing areas ripe for further inquiry, this review aspires to inform clinical decision-making regarding the management of OSA-related AF.